In vitro and in vivo Synergistic Effects of Florfenicol and Thiamphenicol in Combination Against Swine Actinobacillus pleuropneumoniae and Pasteurella multocida - Rattanapanadda, Porjai; Kuo, Hung-Chih; Vickroy, Thomas W.; Sung, Chi-Hsuan; Rairat, Tirawat; Lin, Tsai-Lu; Yeh, Sze-Yu; Chou, Chi-Chung (Frontiers in Microbiology, 2019)
Potential synergism between florfenicol (FF) and thiamphenicol (TAP) was investigated for in vitro efficacy against Actinobacillus pleuropneumoniae and/or Pasteurella multocida as well as in vivo efficacy in swine. Among isolates of A. pleuropneumoniae (n = 58) and P. multocida (n = 79) from pigs in Taiwan that were tested, high percentages showed resistance to FF (52 and 53%, respectively) and TAP (57 and 53%, respectively). Checkerboard microdilution assay indicated that synergism [fractional inhibitory concentration index (FICI) ≤ 0.5] was detected in 17% of A. pleuropneumoniae (all serovar 1) and 24% of P. multocida isolates. After reconfirming the strains showing FICI ≤ 0.625 with time kill assay, the synergism increased to around 32% against both bacteria and the number could further increase to 40% against resistant A. pleuropneumoniae and 65% against susceptible P. multocida isolates. A challenge-treatment trial in pigs with P. multocida showed that the FF + TAP dosage at ratios correspondent to their MIC deduction was equally effective to the recommended dosages. Further on the combination, the resistant mutation frequency is very low when A. pleuropneumoniae is grown with FF + TAP and similar to the exposure to sub-inhibitory concentration of FF or TAP alone. The degree of minimum inhibitory concentration (MIC) reduction in FF could reach 75% (1/4 MIC) or more (up to 1/8 MIC for P. multocida, 1/16 for A. pleuropneumoniae) when combined with 1/4 MIC of TAP (or 1/8 for A. pleuropneumoniae). The synergism or FICI ≤ 0.625 of FF with oxytetracycline (47%), doxycycline (69%), and erythromycin (56%) was also evident, and worth further investigation for FF as a central modulator facilitating synergistic effects with these antimicrobials. Taken together, synergistic FF + TAP combination was effective against swine pulmonary isolates of A. pleuropneumoniae and P. multocida both in vitro and in vivo. Thus, this study may offer a potential alternative for the treatment of A. pleuropneumoniae and P. multocida infections and has the potential to greatly reduce drug residues and withdrawal time.